Synthesis of Sr2Nb3O10 nanosheets and their application for growth of thin film using an electrophoretic method. Issue 3 (30th December 2016) - Lee, Woong‐Hee; Im, Mir; Kweon, Sang‐Hyo; Woo, Jong‐Un; Nahm, Sahn; Choi, Ji‐Won; Hwang, Seong‐Ju
Abstract: K(Sr2 Nb3 )O10 (KSN) ceramic without the secondary phase was obtained from a KSN + 0.05K2 O specimen sintered at 1350°C. This ceramic was used as the precursor to synthesize Sr2 Nb3 O10 − (SNO − ) nanosheets, because it has a pure KSN phase with a large (002) plane. The SNO − nanosheets were deposited on a Pt/Ti/SiO2 /Si substrate using the electrophoresis method at room temperature, and heated at various temperatures to get rid of the organic defects. The crystalline SNO phase without organic defects was formed in film annealed at 600°C. However, when the annealing temperature exceeded 600°C, the Pt electrode became unstable, resulting in degradation of the SNO film. Good electric properties were obtained from the SNO film annealed at 600°C: dielectric constant of 70, dielectric loss of 0.017 at 1.0 MHz, leakage current density of 3.5×10 −8  A/cm 2 at 0.2 MV/cm, and a breakdown electric field of 0.25 MV/cm.